2006
DOI: 10.1002/jsfa.2525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the stage of growth, wilting and inoculation in field pea (Pisum sativum L.) silages. I. Herbage composition and silage fermentation

Abstract: Effect of the stage of growth, wilting and inoculation in field pea (Pisum sativum L.) silages. I. Herbage composition and silage fermentationAbstract: The stage of growth, field wilting and inoculation with lactic acid bacteria (LAB) effects were studied by ensiling herbage of field pea (Pisum sativum L.) at four consecutive stages. Stands of semi-leafless field pea, sown in spring, were harvested at four progressive morphological stages (end of flowering, I; beginning of pod filling, II; advanced pod filling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
5
8
0
Order By: Relevance
“…The wilting reduced the protein degradation in all the silages, except in stage II, by decreasing the NPN, NH 3 ‐N and the free AA concentrations, as observed in lucerne 23. The ammonia level was never higher than 140 g kg −1 , as expected with a lactic acid‐dominated fermentation,2 and was notably reduced by inoculation, by a factor of 2–3, in all the silages except at stage I. This effect has been thoroughly described for inoculated silages made from several grass and legume crops 26.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The wilting reduced the protein degradation in all the silages, except in stage II, by decreasing the NPN, NH 3 ‐N and the free AA concentrations, as observed in lucerne 23. The ammonia level was never higher than 140 g kg −1 , as expected with a lactic acid‐dominated fermentation,2 and was notably reduced by inoculation, by a factor of 2–3, in all the silages except at stage I. This effect has been thoroughly described for inoculated silages made from several grass and legume crops 26.…”
Section: Discussionsupporting
confidence: 64%
“…The trial was carried out in 2001 to study the effects of wilting and inoculation with LAB on the ensiling of peas cut at four progressive morphological stages (end of flowering, stage I; beginning of pod filling, stage II; advanced pod filling, stage III; beginning of ripening, stage IV). The crop characteristics, the experimental design and the sampling procedures are described in Part I 2…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adesogan and Salawu (2004) found that FA applied at a rate of 2·5 g kg −1 significantly decreased ammonia‐N concentration of FP silage compared to an inoculant ( L. buchneri , L. plantarum , Pediococcus pentosaceus ), although not below 80 g kg −1 N. However, they observed that in wheat–pea mixtures protein breakdown was more effectively restricted by the inoculant than by FA. Borreani et al. (2006) observed that, compared to untreated silage, L. plantarum significantly reduced protein breakdown in unwilted FP silage ensiled at the pod‐filling stage but not in silage ensiled at the end of flowering, which was considered to be related to the higher BC of the less mature herbage at the pod‐filling stage.…”
Section: Discussionmentioning
confidence: 93%
“…The earlier harvest material was of much higher nutritive values for ruminants for use as a supplement to N deficient cereal CR for the lactating or fattening animals. As the plant matured from early to final harvest the increase in seed yield, by 42% and 28% in Trial 1 and 2, respectively, was within the range reported by Borreani et al (2006) in field pea as the plant matured from the end of flowering to beginning of ripening and where the contribution of the seed to the DM yield was increased from 0 to 48%. Seeds attain maximum dry weight when they reach physiological maturity (Shaheb et al, 2015;Shaw and Loomis, 1950;Tekrony and Egli, 1997).…”
Section: Effect Of Crop Growth Stage At Harvest On Seed and Haulm Yiesupporting
confidence: 57%